Hotspots and frontier trends of diabetic associated cognitive decline research based on rat and mouse models from 2012 to 2021: A bibliometric study - Li, Jie; Wang, Zhen; Nan, Xinyu; Yin, Mingjie; Fang, Hui (Frontiers in Neurology, 2022)
Background The establishment of rodent models, such as rat and mouse models, plays a critical role in the study of diabetic associated cognitive decline. With the continuous growth of relevant literature information, it is difficult for researchers to accurately and timely capture the topics in this field. Therefore, this study aims to explore the current status and frontier trends of diabetic associated cognitive decline research based on rat and mouse models through a bibliometric analysis. Methods We collected 701 original articles on this subject from the Science Citation Index Expanded of the Web of Science Core Collection from 2012 to 2021. Then we utilized CiteSpace and VOSviewer for plotting knowledge maps and evaluating hotpots and trends. Results During this decade, except for a slight decline in 2020, the number of annual outputs on diabetes associated cognitive decline research using rat and mouse models increased every year. China (country), China Pharmaceutical University (institution), Gao, Hongchang (the author from the School of Pharmacy of Wenzhou Medical University, China), and Metabolic Brain Disease (journal) published the most papers in this research field. The analysis results of co-cited references and co-occurrence keywords indicated that “mechanisms and prevention and treatment methods”, especially “oxidative stress”, “potential association with Alzheimer's disease” and “spatial memory” are research focuses in this subject area. The bursts detection of references and keywords implied that “cognitive impairment of type 1 diabetes” and “autophagy and diabetes associated cognitive decline” will be potential directions for future research in this subject area. Conclusion This study systematically assessed general information, current status and emerging trends of diabetic associated cognitive decline research using rat and mouse models in the past decade based on a bibliometric analysis. The number of publications was annually increasing although a slight decline was observed in 2020. Contributions from different countries/regions, institutions, authors, co-cited authors, journals and co-cited journals were evaluated, which may also be used to guide future research. Through the analysis of references and keywords, we predicted the future research hotspots and trends in this field.